2018
DOI: 10.1093/cercor/bhy226
|View full text |Cite
|
Sign up to set email alerts
|

Use-Dependent Plasticity in Human Primary Motor Hand Area: Synergistic Interplay Between Training and Immobilization

Abstract: Training and immobilization are powerful drivers of use-dependent plasticity in human primary motor hand area (M1HAND). In young right-handed volunteers, corticomotor representations of the left first dorsal interosseus and abductor digiti minimi muscles were mapped with neuronavigated transcranial magnetic stimulation (TMS) to elucidate how finger-specific training and immobilization interact within M1HAND. A first group of volunteers trained to track a moving target on a smartphone with the left index or lit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 71 publications
5
40
0
1
Order By: Relevance
“…Specifically, ADM muscle was located more medially (p=0.005) and superiorly (p=0.005) relative to the hotspot of the FDI muscle. This finding replicates our previous sulcus-aligned mapping studies, using a single line of targets placed at the caudal border of the precentral crown (27,33,34). Finally, ANOVA also revealed main effects of the two within-subject factors group (F(1,22)= 47.491, p<0.001) and coordinates (F(2,44)= 251.644, p< 0.001).…”
Section: Precentral Corticomotor Mappingsupporting
confidence: 89%
See 2 more Smart Citations
“…Specifically, ADM muscle was located more medially (p=0.005) and superiorly (p=0.005) relative to the hotspot of the FDI muscle. This finding replicates our previous sulcus-aligned mapping studies, using a single line of targets placed at the caudal border of the precentral crown (27,33,34). Finally, ANOVA also revealed main effects of the two within-subject factors group (F(1,22)= 47.491, p<0.001) and coordinates (F(2,44)= 251.644, p< 0.001).…”
Section: Precentral Corticomotor Mappingsupporting
confidence: 89%
“…This is problematic because the angle at which the electrical current "hits" the precentral gyrus has strong impact on the TMS-induced electric field (32). These considerations prompted us to develop a sulcus-aligned TMS mapping procedure which adjusts the orientation of the TMS coil at each mapping site to the local curvature of the precentral gyrus (27,33,34). The procedure exploits the fact that the motor hand representation in the precentral gyrus can be readily identified on structural MRIs by its characteristic knob-like shape (35).…”
Section: Sulcus-aligned Tms Mapping Of the Motor Hand Knobmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, a recent study showed that motor learning leads to a reorganization of both trained and untrained representations in M1 (Raffin and Siebner, 2019). While this broad increase in CS excitability does not seem to be ubiquitous across studies (Muellbacher et al, 2001; Bologna et al, 2015), different factors may influence the breadth of cortical plasticity, including the type of movement executed (Muellbacher et al, 2001), the duration of training (Classen et al, 1998) and the mechanical constrains applied on the untrained effectors (Raffin and Siebner, 2019). Still, our findings favor the view that motor training, even in very simple tasks, is associated with a broad functional reorganization in M1, affecting both trained and untrained motor representations.…”
Section: Discussionmentioning
confidence: 99%
“…Its ability to localize motor eloquent cortical areas has found successful applications in preoperative planning [4,5]. Additionally, a growing body of literature is concerned with the use of nTMS mapping for assessing the state of the motor system and its plastic changes during learning of new skills [69], in neurological diseases, such as stroke [10], dystonia [11], spinal cord injury [12,13], amyotrophic lateral sclerosis [14], as well as in the course of treatment [15]. For identifying the possibly subtle differences in motor maps, it is essential to make the method precise and reliable.…”
Section: Introductionmentioning
confidence: 99%